Place', space' and dialogue': conceptualising dialogic spaciality in English faith-based universities - Su, Feng (Journal of beliefs and values, 2018)
This article proposes a conceptualisation of dialogic spaciality, and advances our understandings of the dynamic interplay of dialogic space (where meaningful conversations take place) and place (a geographic location) and the influence these have on academic life. The conceptualisation is developed from a qualitative study which focused on the relationship of dialogue, space and intellectual encounters in faith-based higher education settings in England. The article highlights the significance of dialogue in these institutions because of the emphasis traditionally placed on conversation in the Christian university tradition. It concludes that dialogic spaciality may counter elements of non-reflexive and performative ethos as something that is transferable to other universities.